ANALYSIS OF STUDENTS SATISFACTION INDEX OF FKIP UNTAN ON MERDEKA BELAJAR KAMPUS MERDEKA (MBKM) - Reiki Nauli Harahap (Akademika, 2023)
Merdeka Belajar Kampus Merdeka (MBKM) is one of the government's policies in the field of education. MBKM opened a new paradigm of education implementation. MBKM is an educational innovation to ensure that the learning process is inclusive and in accordance with the times. MBKM is expected to have a significant impact on the actors that involved in the education ecosystem, including students. The purpose of this study was to measure the impact of MBKM based on the level of student satisfaction at the Faculty of Teacher Training and Education (FKIP) Universitas Tanjungpura. This paper uses quantitative methods. Data collection was carried out using a questionnaire and interviewing 44 respondents. The research hypothesis is that student satisfaction with MBKM has an impact on the impact of MBKM. The results of this study were that the implementation of MBKM at FKIP UNTAN obtained a score of 3,795 with a percentage of 75,907. This value is included in the “satisfactory” category, so it can be concluded that the MBKM program has a significant impact on students at FKIP UNTAN